Neuroprotective effect of melatonin on glucocorticoid toxicity in the rat hippocampus - Furio, Analía Mabel (2008)
Dexamethasone has a neurotoxic action on rodent hippocampus. The objective of this study was to examine the extent of neuroprotection exerted by melatonin on that neurotoxic effect. A group of 24 rats received 9 daily subcutaneous injections of 0.5 mg/kg of dexamethasone. Half of them received 25 ìg/ml of melatonin in the drinking water for 10 days. Controls included rats injected with vehicle or rats injected with vehicle plus melatonin in the drinking water. At the end of treatment, the brains were processed for a morphometric analysis, the results being expressed as percent number of abnormal hipoccampal neurons (defined as necrotic cells) per field. Melatonin decreased by 77 % the effect of dexamethasone (p< 0.001). A laterality of neurotoxic effect of dexamethasone was apparent in rats that did not receive melatonin (percent of necrotic cells in left and right hippocampus: 32.0 ± 4.4 and 19.6 ± 1.9 %, respectively, p< 0.01). The results indicate a protective effect of melatonin on glucocorticoid neurotoxicity in the rat hippocampus.